Reforming end-user energy prices could rationalize GCC energy demand - Krane, J (Oxford Institute for Energy Studies, 2015)
The six GCC economies – Saudi Arabia, the UAE, Oman, Kuwait, Qatar, and Bahrain – are some of the world’s most profligate consumers of energy and emitters of greenhouse gases, relative to their size. Other hydrocarbon exporters in the region, notably Iran and Algeria, are beset by similar circumstances. Observers have attributed this state of affairs to the very low prices at which energy is sold in these countries. However, there have been few attempts to quantify the effects of subsidies on domestic consumption. This article takes a simplified approach to a complex topic by posing the following questions: What would happen if fuel and electricity prices in the Gulf monarchies were increased to world market levels? How would consumers respond? More specifically, would electricity demand in Abu Dhabi adjust to look more like that in unsubsidized, but otherwise similar, Arizona?